Rechtsfragen bei Open Science Ein Leitfaden - Kreutzer, Till (Hamburg University Press, 2019)
Digitisation makes open science possible. This has many aspects, in particular free access to academic publications and materials (Open Access), transparent peer review procedures (Open Peer Review) or open source technologies (Open Source). Supporting open science in Hamburg as a research location is the aim of the framework Hamburg Open Science. The guidelines developed in this context are intended to make this ecosystem legally tangible. In the first part, the guidelines systematically develop the areas of law concerned. The second part answers legal questions on Open Science that come directly from universities and libraries. In this way, a practice-oriented preparation and mediation can be achieved. The authors of the guide are Dr. Till Kreutzer, partner of the law office iRights.Law, and Henning Lahmann, research associate at iRights.Law.